1996
DOI: 10.1016/0003-4878(96)00003-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of contaminant source location on worker exposure in the near-wake region

Abstract: The exposure of workers in the near-wake region due to a recirculating airflow was studied experimentally and numerically. A mannequin was installed in an open-ended tunnel and tracer gas was released at several locations downstream to determine the size and location of the reverse flow region. The contaminant transport into the breathing zone was found to depend strongly on the location of the release point. The airflow field was also determined numerically assuming a steady flow and using the standard k-epsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…In agreement with Malek, (5) Kim and Flynn (14) and Kulmala et al, (19) concentrations near the chest were higher than concentrations at the nose. Values of C chest in this study were almost always (34 of 36 samples) higher than the corresponding C nose values.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In agreement with Malek, (5) Kim and Flynn (14) and Kulmala et al, (19) concentrations near the chest were higher than concentrations at the nose. Values of C chest in this study were almost always (34 of 36 samples) higher than the corresponding C nose values.…”
Section: Discussionsupporting
confidence: 88%
“…In nearly all Back orientation cases, as velocity increased, measured concentrations at all five sampler locations increased exponentially (Figures 3 and 4). That appears to disagree with the findings of Kim and Flynn (14) and Kulmala et al, (19) who found decreasing concentrations at increasing velocities. The findings cannot be compared directly with Kim and Flynn due to the much lower velocities in this study, but the highest two velocities overlap those in Kulmala et al The measured chest concentrations for both studies were taken at points in a horizontal plane in front of the mannequin rather than on the body of the mannequin, so the C chest results may not be directly comparable.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Kim and Flynn (1991) observed experimentally a strong downwash above chest level for an isothermal mannequin. Kulmala et al (1996) found a mean recirculation length of 1.5 diameter behind a mannequin, which depended little on the freestream velocity. Edge et al (2005) confirmed by RANS the existence of a recirculation region behind the torso, contributed by asymmetric vortex shedding.…”
Section: Wake Dynamics In Finite Bluff Body Flowsmentioning
confidence: 91%
“…Studies investigated the effects of cross draft velocities on airflow patterns around a worker (Fletcher and Johnson, 1996;Kim and Flynn, 1992;Kulmala et al, 1996;Welling et al, 2001;Heist et al, 2003). They found that recirculation length downstream of the manikin (wake zone) depended on cross draft velocities and can be estimated using the manikin 1/2 dimensions.…”
Section: Manikins: Unheated and Non-breathingmentioning
confidence: 99%